Conserved function of a RasGEF-mediated pathway in the metabolic compensation of the circadian clock - Sárkány, Orsolya; Szőke, Anita; Pettkó-Szandtner, Aladár; Kálmán, Eszter Éva; Brunner, Michael; Gyöngyösi, Norbert; Káldi, Krisztina (The FEBS journal, 2025)
Metabolic compensation of the circadian clock ensures endogenous timing across a broad range of nutrient conditions, enabling organisms to adapt efficiently to recurrent environmental changes, even during nutrient scarcity. In this study, we have identified a novel clock-controlled gene, rasgef (Rat Sarcoma Guanine Nucleotide Exchange Factor), that plays a crucial role in modulating the circadian clock under starvation conditions in the circadian model organism Neurospora crassa. The gene product, RasGEF—a nucleotide exchange factor for the small G protein RAS2P (Rat Sarcoma 2 Protein)—displays glucose-dependent phosphorylation and localization. We show that deletion of rasgef hinders metabolic compensation of the circadian clock to glucose-depleted conditions and disrupts the rhythmic expression of the output gene ccg2. Furthermore, we demonstrate in osteosarcoma cells that the period of the mammalian clock is also compensated across a wide range of extracellular glucose levels and adaptation of the clock to glucose-starved conditions depends on the RasGEF homolog SOS1 (Son of Sevenless 1) and its downstream signaling component ERK (Extracellular Signal-Regulated Kinase). Our results suggest a conserved role of RasGEF-mediated signaling in the maintenance of circadian rhythm under glucose-limited conditions.
Online verfügbar: 02. Mai 2025
Gesehen am 29.10.2025